Equity and capacity to benefit from early access to medicines schemes - Sarah J. L. Edwards; Paul Aliu; Joe Brierley; Søren Holm; Peter J. Pitts (International Journal for Equity in Health)
Abstract Many diseases, especially rare ones, have not gained the attention or support needed to attract dedicated research interest to be able to develop successful medicines. There is, thus, a significant unmet clinical need, not all of which is (or indeed can be) addressed through the evaluation of investigational treatments introduced within the confines of clinical trials. People with severe life-threatening conditions who are not eligible to participate in any ongoing clinical trials may be able to try investigational medicines through schemes facilitating early use of or expanded access to innovative medicines. Here, we focus on the issue of equity in such programmes. Standard metrics of clinical need which inform operational decisions about equity in resource allocation primarily rely on social goods which have already been evaluated, providing evidence to support the standard assessment of patient ‘capacity to benefit’ from given medical interventions. Notions of equity have only relatively recently been discussed within research and innovation generally and within the ethics of clinical trials in particular. Considerations of equity, however, require an overview of all these different patient pathways. We suggest that a new formal method to assess eligibility for early use of or expanded access to innovative medicines be used to capture both the severity of the condition and capacity for scientific or social value alongside clinical trials.